The prevalence and risk factors of anxiety in multiple sclerosis: A systematic review and meta-analysis - Zhang, Xiaoyun; Song, Ying; Wei, Zhiqiang; Chen, Xiao; Zhuang, Xiaojia; Yi, Li (Frontiers in Neuroscience, 2023)
Background: Patients with multiple sclerosis (MS) suffer from repetitive neurological deterioration, while anxiety may play a significant role in the disease's progression. Objective: To explore the prevalence of anxiety in MS and to investigate the risk factors related to anxiety in MS patients. Methods: The prevalence or risk factors of anxiety in MS published before May 2021 have been systematically screened in four databases. Results: In total, 32 studies were found to be eligible. Anxiety prevalence was estimated to be 36% based on the pooled estimates (The 95% confidence interval (CI) = [0.30–0.42], I2=98.4%). Significant risk factors for developing of anxiety were as follows: age at survey (The weighted mean difference (WMD) = 0.96, 95% CI = [0.86 - 1.06], I2=43.8%), female (The odd ratio (OR) = 1.78, 95% CI=[1.38–2.30], I2=0%), living together (OR 2.83, 95% CI=[1.74–4.59], I2=0%), past psychiatric history (OR 2.42, 95% CI=[1.56–3.75], I2=0%), depression (OR 7.89, 95% CI=[3.71–16.81], I2=0%), not taking MS medication (OR 2.33, 95% CI=[1.29–4.21], I2=77.8%), relapsing-remitting MS (RRMS) (OR 1.50, 95% CI=[0.94–2.37], I2=53.5%) and baseline Expanded Disability Status Scale (EDSS) (OR 0.84, 95% CI=[0.48–1.21], I2=62.2%). Conclusion: An estimated 36% of people with MS suffer from anxiety. And anxiety rates in MS patients are significantly associated with age, gender, living together, prior psychiatric history, depression, drug compliance, RRMS, and baseline EDSS.